Identification and Characterization of IgE‐Reactive Proteins and a New Allergen (Cic a 1.01) from Chickpea (Cicer arietinum). Issue 19 (21st September 2020) - Wangorsch, Andrea; Kulkarni, Anuja; Jamin, Annette; Spiric, Jelena; Bräcker, Julia; Brockmeyer, Jens; Mahler, Vera; Blanca‐López, Natalia; Ferrer, Marta; Blanca, Miguel; Torres, Maria; Gomez, Paqui; et al.
Abstract : Scope: Chickpea ( Cicer arietinum ) allergy has frequently been reported particularly in Spain and India. Nevertheless, chickpea allergens are poorly characterized. The authors aim to identify and characterize potential allergens from chickpea. Methods and Results: Candidate proteins are selected by an in silico approach or immunoglobuline E (IgE)‐testing. Potential allergens are prepared as recombinant or natural proteins and characterized for structural integrity by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS‐PAGE), circular dichroism (CD)‐spectroscopy, and mass spectrometry (MS) analysis. IgE‐sensitization pattern of Spanish chickpea allergic and German peanut and birch pollen sensitized patients are investigated using chickpea extracts and purified proteins. Chickpea allergic patients show individual and heterogeneous IgE‐sensitization profiles with extracts from raw and boiled chickpeas. Chickpea proteins pathogenesis related protein family 10 (PR‐10), a late embryogenesis abundant protein (LEA/DC‐8), and a vicilin‐containing fraction, but not 2S albumin, shows IgE reactivity with sera from chickpea, birch pollen, and peanut sensitized patients. Remarkably, allergenic vicilin, DC‐8, and PR‐10 are detected in the extract of boiled chickpeas. Conclusion: Several IgE‐reactive chickpea allergens are identified. For the first time a yet not classified DC‐8 protein is characterized as minor allergen (Cic a 1). Finally, the data suggest a potential risk for peanut allergic patients by IgE cross‐reactivity with homologous chickpea proteins. Abstract : Chickpeas ( Cicer arietinum ) frequently can cause immunoglobuline E (IgE)‐mediated hypersensitivity reactions. However, chickpea allergens are poorly characterized. Using a molecular and biochemical methods, IgE‐reactive chickpea allergens are identified. Emphasizing the charcterization of a yet not classified DC‐8 protein as minor allergen (Cic a 1). Finally, data provide evidence for potential risk for peanut allergic patients by IgE‐cross‐reactivity with homologous chickpea proteins.